Implementation of the Dikyasa Unit of the Bandung Polrestabes Traffic Unit in Overcoming Traffic Congestion through Traffic Management and Engineering in the Sukajadi Area (Indonesian Journal of Police Studies, 2024)
In the background by the existence of traffic congestion problems that occur in the Sukajadi area of the city of Bandung. Congestion occurs because the sukajadi road is a fairly congested and crowded road that is traversed by the community in the city of Bandung, and there are several factors that cause congestion. Related to this, traffic congestion is needed by the Bandung Police Traffic Unit through traffic management and engineering. The results of the study found that the situation and condition of the traffic flow in the Sukajadi area were jammed at certain times, namely in the morning when the community left for work and in the afternoon when the community returned home from work. Factors causing traffic congestion are the Paris Van Java shopping center, crossroads or small alleys, the surge in the number of vehicles during holidays, Efforts to deal with congestion by placing members of the Bandung Traffic Police Unit to carry out arrangements and conduct traffic management and engineering, and implementing traveling lighting and coordination with relevant agencies. The theory used in this study uses Management Theory and Policy Implementation Theory. The concepts used are the Concept of Implementation, the Concept of Traffic and the Concept of Management and Traffic Engineering. This research was conducted using a qualitative approach using descriptive analysis research methods, data collection techniques by interviewing, observing and studying documents, as well as validating data using triangulation of data sources, triangulation of techniques and triangulation of time, for technical data analysis using data reduction, data presentation and Verification or conclusion. Based on the results of the study, the author's conclusion is that the Implementation of the Traffic Unit Unit of the Bandung Polrestabes Traffic Unit in overcoming congestion has not been optimal, because kamseltibcarlantas has not yet been realized in the Sukajadi Area. So the authors provide advice to the Bandung Police Traffic Unit to coordinate with related agencies more intensively, increase the number of personnel so that performance is more optimal, make standard operating procedures in handling congestion, install CCTV to control traffic flow control, and coordinate with related agencies for the realization and congestion in the Sukajadi region.
Keywords: tes